Antituberculosis in pregnancy: a review (Research, Society and Development, 2020)
Tuberculosis is a contagious disease that primarily affects the lungs, being triggered by Mycobacterium tuberculosis, presenting difficult treatment especially during pregnancy due to the existence of risks to the pregnant woman and the fetus. This study aimed to conduct a literature review related to the use of antituberculosis drugs in pregnancy, highlighting the possible risks. The search for articles occurred in the Lilacs, PubMed, Science Direct and Periodical CAPES databases, including only those published between the years 2005 to 2019. In Brazil, treatment is done primarily through rifampicin, isoniazid, pyrazinamide and ethambutol , and as second-line drugs are aminoglycosides, quinolones and fluorquinolones. Rifampicin has a congenital anomaly rate two to three times higher when compared to isoniazid and ethambutol; isoniazid is recommended as chemoprophylaxis in pregnant women with positive sputum smear microscopy and/or diagnosed with hematogenous disseminated tuberculosis; ethambutol has not been associated with any type of malformation, whereas pyrazinamide is not recommended during pregnancy. Aminoglycosides, quinolones and their derivatives, are associated with malformations and embryotoxicity, and their use is discouraged. Thus, due to the literary scarcity related to the risks associated with the use of antituberculosis drugs during pregnancy, it is necessary to develop cohort studies that bring information about these drugs in the different trimesters of pregnancy.